Reanna Nelson: capstone - Nelson, Reanna, artist (Colorado State University. Libraries, 2016)
The artist's statement: I am interested in the complex interactions we have with the landscape around us. The metaphorical meeting places between humans and our environment - the connections we form with the land, the use and management decisions that are made, the effect that natural disasters have on us - reveal that changes made to the land are never purely ecological, but are reflections of culture. My work recognizes the dual view we tend to have of the natural environment as both a resource for us to use and as an untouched place to be preserved. While there are increasing uncertainties about what purpose nature should serve and what our role in the landscape should be, it is true that the way we perceive the land is inextricably linked to the values we place upon it and ultimately the decisions we make about its treatment.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: drawing; sculpture